Governance, its determinants, and firm performance: An evidence from the top UK charities - Yang, Bitian (2019)
During the past twenty years, research on corporate governance, the determinants of corporate governance, and firm performance has been widely studied. However, this research mainly focuses on the profit-making sector. It has been given little focus on the governance of non-profit organisations. Therefore, this study examines the determinants of governance and the relationship between these determinants and performance in charities. To be more specific, this study focuses on the questions as shown below: